Excess deaths from non-COVID-19-related causes in Japan and 47 prefectures from January 2020 through May 2021 by place of death. (September 2022) - Nomura, Shuhei; Eguchi, Akifumi; Ghaznavi, Cyrus; Tanoue, Yuta; Kawashima, Takayuki; Yoneoka, Daisuke; Yamasaki, Lisa; Suzuki, Motoi; Hashizume, Masahiro
Abstract: Excess deaths, including all-causes mortality, were confirmed for the first time in Japan in April 2021. However, little is known about the indirect effects of COVID-19 on the number of non-COVID-19-related deaths. We then estimated the excess deaths from non-COVID-19-related causes in Japan and its 47 prefectures from January 2020 through May 2021 by place of death. Vital statistical data on deaths were obtained from the Ministry of Health, Labour and Welfare. Using quasi-Poisson regression models, we estimated the expected weekly number of deaths due to all-causes excluding COVID-19 (non-COVID-19) and due to respiratory disease, circulatory disease, malignant neoplasms, and senility. Estimates were made separately for deaths in all locations, as well as for deaths in hospitals and clinics, in nursing homes and elderly care facilities, and at home. We defined a week with excess deaths as one in which the observed number of deaths exceeded the upper bound of the two-sided 95% prediction interval. Excess death was expressed as a range of differences between the observed and expected number of deaths and the 95% upper bound of the two-sided predictive interval. The excess percentage was calculated as the number of excess deaths divided by the expected number of deaths. At the national level, excess deaths from non-COVID-19-related all-causes were observed during April 19 to May 16, 2021. The largest excess percentage was 2.73–8.58% (excess deaths 689–2161) in the week of May 3–9. Similar trends were observed for all four cause categories. The cause-of-death categories which contributed to the excesses showed heterogeneity among prefectures. When stratified by place of death, excess mortality tended to be observed in nursing homes and elderly care facilities for all categories, in hospitals and clinics for circulatory disease, and at home for respiratory disease, malignant neoplasms, and senility. A caution is necessary that for the lastest three months (March–May 2021), adjusted data were used to account for possible reporting delays. Highlights: There are few studies on excess deaths due to non-COVID-19-related causes. Since April 2021, excess deaths from all causes other than COVID-19 have been observed in Japan. Excess mortality tended to be observed in nursing homes and elderly care facilities for all categories. These excesses have lasted for multiple, consecutive weeks, aligning with the fourth wave of COVID-19.